Study of the variability in 28 spontaneous populations of Trifolium tomentosum L.: relations with factors of the environment of origin - Issolah R.; Abdelguerfi A. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
As part of the valorization of local fodder resources, several spontaneous clovers (genus Trifolium) may be used to reduce erosion and improve grazing on marginal areas. This study focuses on the behaviour and biometrical characters of 28 spontaneous populations of T.tomentosum. The populations manifested a certain variability that could be linked to ecological factors of their environment of origin (rainfall, altitude, longitude, latitude). The longitude followed by the rainfall were the environmental factors most correlated with the different morphological and growth characters.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)